Karakteristik Gambaran Elektroensefalografi Pada Pasien Kejang Pascastroke : Sebuah Studi Retrospektif - Nafiah, Risqon (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2024)
Introduction: Stroke is the second leading cause of death in the world with many complications, including seizures and epilepsy. Post-stroke epileptic seizures can occur either in the acute phase or in the late phase of stroke. Electroencephalography (EEG) examination, a non-invasive diagnostic method, plays an important role for the diagnosis of post-stroke seizures. Aim: This retrospective study aims to investigate the characteristic of EEG in post-stroke seizures patients. Methods: This study analyzed EEG data of post-stroke seizure patients between 2019-2023. Inclusion criteria was history of motor seizures, while exclusion criteria were history of previous seizures or epilepsy and having severe metabolic disorders. Results: Seventy six post-stroke seizure patients were analyzed in this study. 78.9% were post ischemic stroke, while 21.1% were hemorrhage stroke. There were 23.7% normal EEG, while the remaining 72.3% showed abnormal EEG, consist of 19.7% abnormal EEG II and 56.6% abnormal EEG III. Discussion: There were no significant differences found in the characteristics of post-stroke seizures (such as age, gender, EEG classification, and EEG abnormalities). However, there is a significant difference in the presence of sharp-spike waves between post-ischemic stroke seizures and post-hemorrhagic stroke seizures, while sharp-spike waves are identified as one of the risk factors for recurrent post-stroke seizures. Keywords: Stroke, electroencephalography, post stroke seizure